Palm Springs Spa Hotel and Mineral Springs [postcard] (Fran Hunt Color Productions, Inc.)
Caption on back reads: 'Palm Springs Spa Hotel and Mineral Springs, Indian Ave. and Tahquitz-McCallum Drive, Palm Springs, California 92262. The most beautiful spa in the world. Utilizing the centuries old famous hot natural mineral water springs of the Agua Caliente Indians.'